User-centered evaluation of privacy models for protecting personal medical information - Samsuri, Suhaila; Ismail, Zuraini; Ahmad, Rabiah (Springer Berlin Heidelberg, 2011)
Privacy has always been a crucial element in the management of personal medical information. It warrants a comprehensive model during the designing stage of the management system in order to conserve the security of the information. One of the key success factors in protecting the privacy of information is measured by the ability of the users in controlling the flow of the information in the system. This research concentrates on the integrated models of privacy protection for health information environment which can be applied as guidance while designing a secured electronic medical record for health information system (HIS). The system’s effectiveness that uses this integrated model is suggested to be evaluated with the user-centred evaluation model (UPEM). This privacy protection model outlined four important components which were based on the findings from the interviews conducted namely legislation, ethic, technology and culture.